COMMUNITY DEVELOPMENT BASED ON THE GREAT MOSQUE [CASE STUDY OF AL-BARKAH, BEKASI MOSQUE] DAKWAH AND THE DEVELOPMENT OF ISLAMIC COMMUNITIES - Luthfiyyah, Neneng; Uyuni, Badrah (Spektra: Jurnal Ilmu-ilmu Sosial, 2019)
Mosques have a strategic function in Islamic society. Apart from being a place of worship, the mosque also functions as a medium for guiding people in a holistic manner. Rasulullahh SAW built the first mosque in the city of Medina with the aim of enlightening the people and introducing divine messages. Mosques are not only used for carrying out ceremonial worship activities such as congregational prayers, dzikir, reading the Koran, and praying but can also be used to carry out socio-religious activities in an effort to develop an Islamic community (Yani, 2007: 5). Even today The existence of a mosque is very potential, especially in empowering Muslims for every aspect of their life. The existence of a reading slogan for a mosque was the initial inspiration for the spirit to restore the glory of Islam from the mosque. History has proven that a Rasulullah GERGAJI chose to build a mosque as the first step in his intention to build a civil society. The concept of a mosque at that time was not only a place of prayer, or a gathering place for certain community groups (tribes), but a mosque was a central place for all public activities, namely the center of education, politics, economy, social and culture. Based on the example of the Prophet, mosques are a major part of the development of Muslims. This shows that mosques in Islam distance are very important in order to foster personalities in particular and Muslims in general (Kurniawan, 2014). The role of mosques for the development of the people is very large and vital. Gazalba (1986) argues that apart from being a center of worship, a mosque is also a center of culture or civilization. The mosque is the first and foremost institution or organization in Islam. The mosque as the center of civilization has a significant role in developing social activities, building the intellectual capability of the people, improving the economy of the people, and becoming a discussion space to find solutions to the current community problems. The importance of the existence of mosques for the Muslim world in Indonesia is indicated by the growing number of mosques and prayer rooms.